Lands. Václav Petrbok, Václav Smyčka (eds.), Tvořeni literaturou. Společné dějiny česky a německy psané literatury českých zemí (1760–1920), Akropolis, Ústav pro českou literaturu AV ČR, Praha 2024, pp. 664 - Németh Vítová, Lenka (Porównania, 2025)
The constitution of modern Czech society included the need to distinguish itself from the “Germanness” dominating the historical Czech territory at the time. The political changes of 1989 led to a new reflection on Czech national and cultural identity, including the relationship with “Germanness”. After several other publications, in 2024 the book Tvořeni literaturou. Společné dějiny česky a německy psané literatury českých zemí (1760–1920) (Created by Literature. The Common History of Czech and German-Language Literature in the Czech Lands, 1760–1920) was published. What sets it apart is the proposed methodology – for the first time an anthropological model (burgher class) is used, which innovatively reveals interactions and interconnections. Showing literature as it was experienced by the mostly bilingual audience of the time is undoubtedly a breakthrough moment.